1986
DOI: 10.2307/1925500
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and Tax Evasion: An Empirical Analysis

Abstract: This paper contains an analysis of the effect of inflation on aggregate tax evasion in the United States over the period 1947-81. It is found that tax evasion in both absolute and relative terms is positively related to the inflation rate. Further, the results indicate that aggregate evasion has risen in both absolute and relative terms with increases in the marginal tax rate, but has fallen with increases in the detection probability, the penalty rate, and the wage share of income. Finally, evasion has risen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1
5

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 11 publications
5
39
1
5
Order By: Relevance
“…17-27) survey the available estimates of tax evasion in large samples of countries. The determinants of tax evasion behavior appear to be roughly consistent across available time series studies (Crane and Nourzad (1986) and Poterba (1987)) and cross-sectional studies (Clotfelter (1983), Slemrod (1985), Witte and Woodbury (1985), Dubin and Wilde (1988), and Feinstein (1991)), and conforms to tax collection patterns in the panel analyzed by Dubin et al (1990). In the only available study of taxpayer behavior in consecutive years, Erard (1992) finds that taxpayers who are audited in one year are more likely than others to be caught evading in the subsequent year.…”
Section: Datasupporting
confidence: 71%
See 2 more Smart Citations
“…17-27) survey the available estimates of tax evasion in large samples of countries. The determinants of tax evasion behavior appear to be roughly consistent across available time series studies (Crane and Nourzad (1986) and Poterba (1987)) and cross-sectional studies (Clotfelter (1983), Slemrod (1985), Witte and Woodbury (1985), Dubin and Wilde (1988), and Feinstein (1991)), and conforms to tax collection patterns in the panel analyzed by Dubin et al (1990). In the only available study of taxpayer behavior in consecutive years, Erard (1992) finds that taxpayers who are audited in one year are more likely than others to be caught evading in the subsequent year.…”
Section: Datasupporting
confidence: 71%
“…16 Value function iterations show that Φ is single valued under weaker conditions than those that follow. Hence Propositions 2.5 and 2.6 hold more generally than the following inequality suggests.…”
Section: Proposition 25 Under the Assumptions Of The Preceding Propomentioning
confidence: 99%
See 1 more Smart Citation
“…Este hecho es consistente con la mayoría de las reflexiones en la literatura sobre el tema, en la que se asegura que es poca la evidencia en cuanto a que los castigos severos reducen el incumplimiento de las obligaciones fiscales (Doob y Webster, 2003 Tercero, las tasas de cumplimiento descienden cuando aumenta la tasa tributaria. El resultado refuta los hallazgos teóricos del modelo de Shlomo Yitzhaki (1974), pero es consistente con diversos estudios empíricos que apoyan la idea de que el ahorro en impuestos derivado del incumplimiento de las obligaciones fiscales es una función de la tasa tributaria (Clotfelter, 1983;Slemrod, 1985;Crane y Nourzad, 1986;Bladry, 1987;Poterba, 1987, y Friedland, Maital y Rutenberg, 1978. En consecuencia, los incentivos para el incumplimiento aumentan en la medida en que se eleva la tasa tributaria.…”
Section: Resultsunclassified
“…As added by Dalu et al (2012) "a country facing an increasing amount of tax evasion and tax avoidance is likely to exhibit a low productive investment mix, this would mean low economic growth and the public run enterprises would be negatively affected." Secondly, Fishburn (1981) and Nourzad (1986) found that the inflation has a positive relationship with the tax evasion as they came to a point that the real value of the income of individual would decline by the influence of the inflation. However, if the individual decided not to pay the tax then he would eventually save his money and his purchasing power for the coming times.…”
Section: The Impact Of Tax Evasionmentioning
confidence: 99%